Growth and Reproduction of Thai Sharpunti (Barbonymus Gonionotus) In the Lentic Water Habitat of Northwest Bangladesh (Journal of Bio-Science, 2023)
This study evaluated the growth and reproductive activity of Thai sharpunti Barbonymus gonionotus in the L-shaped freshwater pond at Rajshahi University campus of northwest Bangladesh during January and August, 2017. Length and weight increment was recorded for the growth study and gonado-somatic index (GSI) with fecundity was estimated for the assessment of reproductive activity. During the study a significant length and weight increment was observed (p